Hellenistic and Roman Sparta - Cartledge, Paul. (London ; New York)
1 online resource (xv, 312 pages)
Keywords: In this new edition, Paul Cartledge and Antony Spawforth have taken account of recent finds and scholarship to revise and update their authoritative overview of later Spartan history, and of the social, political, economic and cultural changes in the Spartan community. This original and compelling account is especially significant in challenging the conventional misperception of Spartan 'decline' after the loss of her status as a great power on the battlefield in 371 BC. The book's focus on a frequently overlooked period makes it important not only for those interested specifically in S.